Personality and Suicidal Behavior in Old Age: A Systematic Literature Review - Szücs, Anna; Szanto, Katalin; Aubry, Jean-Michel; Dombrovski, Alexandre Y. (Frontiers in Psychiatry, 2018)
Background: Suicide rates generally peak in the second half of life and are particularly high in older men, however little is known about the contribution of dispositional factors to late-life suicide. Maladaptive personality traits have been strongly implicated in suicide among younger adults, but the extent to which they continue to play a role in late-life suicidal behavior is unclear. We also do not know whether specific personality profiles interact with the stressors of aging to cause suicidal behavior. Methods: We sought to synthesize the data on personality pathology in late-life suicidal ideation and behavior via a systematic review using the PubMed, Google Scholar, PsycInfo, Scopus, Ovid, Web of Science, Embase and Cochrane search engines. The included key words related to three descriptors: “personality”, “suicide” and “elderly”. Included articles evaluated personality based on the Five-Factor Model or ICD/DSM diagnostic criteria in older samples with minimum age cutoffs of 50 years or older. Our original search identified 1183 articles, of which 31 were retained. Results: Included studies were heterogeneous in their design and personality measurements. Studies of categorical personality disorders were particularly scarce and suggested a stronger association with late-life suicidal ideation than with death by suicide. Only obsessive-compulsive and avoidant personality traits were associated with death by suicide in old age, although in studies that did not control for depression. All personality constructs were positively linked to suicidal ideation, except for histrionic personality, which emerged as a negative predictor. Studies employing the Five-Factor Model also indicated that older adults who died by suicide were less likely to display a maladaptive personality profile than elderly suicide attempters and younger suicide victims, having both lower levels of neuroticism and higher levels of conscientiousness than these comparison groups. Nevertheless, older suicide victims displayed lower levels of openness to experience than younger victims in two samples. Conclusions: Maladaptive personality manifests in milder, sub-threshold and more heterogeneous forms in late-life vs. early-life suicide. An inability to adapt to the changes occurring in late life may help explain the association between suicide in old age and higher conscientiousness as well as obsessive-compulsive and avoidant personality disorders.